2004
DOI: 10.1001/archinte.164.19.2090
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glucose Regulation and Diabetic Complications

Abstract: Atherosclerotic disease accounts for much of the increased mortality and morbidity associated with type 2 diabetes. Epidemiological studies support the potential of improved glycemic control to reduce cardiovascular complications. An association between glycosylated hemoglobin (HbA(1c)) level and the risk for cardiovascular complications has frequently been reported. Most epidemiological data implicate postprandial hyperglycemia in the development of cardiovascular disease, whereas the link between fasting gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
185
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 319 publications
(193 citation statements)
references
References 47 publications
3
185
0
2
Order By: Relevance
“…On the other hand, our results show that diabetic patients with postprandial hyperglycaemia also have daily episodes of significant changes in their vascular tree. This, together with the observation of the effect of postprandial hyperglycaemia on HbA 1c in patients with type 1 diabetes in the Diabetes Control and Complications Trial (DCCT) [41,42], is an additional reason to strictly control daily blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our results show that diabetic patients with postprandial hyperglycaemia also have daily episodes of significant changes in their vascular tree. This, together with the observation of the effect of postprandial hyperglycaemia on HbA 1c in patients with type 1 diabetes in the Diabetes Control and Complications Trial (DCCT) [41,42], is an additional reason to strictly control daily blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial hyperglycaemia has recently been proposed as an independent risk factor for CVD [6,7]. However, the effect of the postprandial state, particularly postprandial hyperglycaemia, on CVD is still a matter of debate [21,22]; studies show that postprandial hyperglycaemia is accompanied by an increase of both oxidative stress and inflammatory markers [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years much attention has been paid to the causal relationship between the postprandial state and atherogenesis [2,3], even in diabetes mellitus [4,5], and it has been suggested that postprandial hyperglycaemia may be an independent risk factor for cardiovascular disease (CVD) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The stored data pairs from each patient include the pre-meal glucose readings with the dates and times of ascertainment. While pre-meal readings were taken on a daily basis, postprandial blood glucose concentrations [15] were also measured, but less frequently.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%